The Antibacterial Activity of Red Betel (Piper crocatum) Leaf Extract toward Staphylococcus aureus - Zulkarnain, Ahmad Alfan Surya Dilaga; Narmada, Ida Bagus; Ardani, I Gusti Aju Wahju (Indonesian Journal of Dental Medicine, 2023)
Background: Red betel (Piper crocatum) is a plant that grows a lot in the tropics, especially Indonesia. The use of red betel Background: Red betel (Piper crocatum) is a plant that grows a lot in the tropical area, especially Indonesia. The use of red betel leaves for medicine is due to the fact that betel leaves contain a lot of essential oils. Purpose: To examine the antibacterial activity of red betel leaf extract against Staphylococcus aureus by investigate at the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values. Methods: This study used an in vitro laboratory experiment as its research method. The post-test only control group design experiment was used in this study, in which the experimental and control groups were not chosen at random and each of the two groups was compared. Results: Red betel leaves that had been extracted at a concentration of 100% were diluted into several concentrations, namely 50%, 25%, 12.5%, 6.25%, and 3.75%. The results of this dilution obtained the minimum inhibitory concentration (MIC) value of red betel leaf extract against Staphylococcus aureus bacteria at a concentration of 6.25%, while the minimum bactericidal concentration (MBC) value was obtained at a concentration of 12.5%. Conclusion: The MBC value in this study was in red betel leaf extract with a concentration of 12.5%, and the MIC value in this study was in red betel leaf extract with a concentration of 6.25%.